Pengaruh Audit Tenure, Kualitas Laba Dan Auditor Spesialisasi Industri Terhadap Audit Delay - Cyntia Aurely; Rina Destiana; Kamalah Saadah (Indonesian Accounting Literacy Journal, 2021)
Audit delay is the time span between the closing date of the financial statements until the date of the independent audited financial report signed by an independent auditor. This research was aimed to examine empirically the effect of audit tenure, earnings quality and auditor industry specialization as independent variables on audit delay as the dependent variable. The data used in this research are financial reports on manufacturing companies in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange in the 2018-2020 period. The selection of this sample using purposive sampling method and then obtained 81 samples of observations. The data analysis method used multiple linear regression analysis. Hypothesis testing on the t statistical test showed that audit tenure had no effect on audit delay, while earnings quality had a positive effect on audit delay, but auditor industry specialization had a negative effect on audit delay.